STANDARDIZATION OF CATIONIC DERIVATIVE OF BAKTERIOPURPURINIMID AS PHARMACEUTICAL SUBSTANCE FOR ANTIMICROBIAL PHOTODYNAMIC THERAPYA - A. M. Frolova (Разработка и регистрация лекарственных средств, 2019)
In this paper key indicators due to Pharmacopoeia XIII [1] that can be used to standardize the cationic derivative of bakteriopurpurinimid as pharmaceutical substance (PS) are presented. The prime application of this compound to be a photosensitiser for antimicrobial photodynamic therapy (PDT).